Amino acid functionalized macroporous gelatin cryogels: Characterization and effects on cell proliferation. (November 2021) - Bayrak, Gülşen; Perçin, Işık; Kılıç Süloğlu, Aysun; Denizli, Adil
Graphical abstract: Highlights: Cryogels were prepared with gelatin and N -methacryloyl-(L)-histidine methyl ester. Average pore size of cryogels was in the range of 18−198 μm. Cryogels showed significant cell viability and enhanced cell proliferation. Abstract: Gelatin and N -methacryloyl-(L)-histidine methyl ester [MAH] containing poly(2-hydroxyethyl methacrylate) [PHEMA] based cryogels were prepared to aid in enhancing cell proliferation. In order to evaluate effects of MAH comonomer and gelatin, cryogels were prepared containing different amounts of gelatin and MAH. Accordingly, four different groups of cryogels which were PHEMA, poly(2-hydroxyethyl methacrylate)-gelatin [PHEMA/GEL], poly(2-hydroxyethyl methacrylate -N- methacryloyl-(L)-histidine methyl ester) [PHEMAH] and poly(2-hydroxyethyl methacrylate -N- methacryloyl-(L)-histidine methyl ester)-gelatin [PHEMAH/GEL] were prepared and a total of eight cryogel groups were obtained depending on the varying gelatin ratios. Swelling tests, scanning electron microscope (SEM), microcomputed tomography (Micro-CT) and Fourier transform infrared spectroscopy- Attenuated Total Reflectance (FTIR-ATR) were performed for characterization studies. FTIR-ATR studies confirmed that gelatin and MAH were incorporated into the cryogel structures. Average pore size of cryogels was in the range of 18−198 μm confirmed by Micro-CT and SEM analysis. Then, cryogels were evaluated for cell proliferation abilities by MTT analysis for 24 h and 48 h for cell viability in L929 mouse fibroblast cells. Cell viability of PHEMAH/0.2GEL cryogels reached 209 %. Interaction and proliferation of fibroblast cells on cryogels demonstrated by SEM examination.